Dynamic Nearest Neighbor Queries in Euclidean Space - NUTANONG, Sarana (Institutional Knowledge at Singapore Management University, 2017)
Given a query point q and a set D of data points, a nearest neighbor (NN) query returns the data point p in D that minimizes the distance DIST(q,p), where the distance function DIST(,) is the L2norm. One important variant of this query type is kNN query, which returns k data points with the minimum distances. When taking the temporal dimension into account, the k NN query result may change over a period of time due to changes in locations of the query point and/or data points.